2017
DOI: 10.1177/1933719117691144
|View full text |Cite
|
Sign up to set email alerts
|

Role of Innate Immunity in Preeclampsia: A Systematic Review

Abstract: Innate immune system dysfunction has been known to be a key player in preeclampsia (PE). Activation of the maternal innate immunity may be triggered by invading microorganisms or endogenous ligands, which are detected by different pattern recognition receptors (PRRs). Although some studies have linked PRR activation to PE, it is still unclear if dysregulated PRR expression is associated with the development of this complication. Therefore, we conducted a systematic review of the literature, searching articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 59 publications
0
25
0
1
Order By: Relevance
“…[128][129][130] For instance, studies have reported decreased IL-35 and IL-9 levels and concurrent drop in CD11c+ myleloid cells and regulatory T cell populations over the course of gestation. 128 Local changes in frequencies, phenotype, and functions of immune cells in the decidua and villi have been attributed in the pathogenesis of several obstetric complications such as preterm labor, 131 PE, [132][133][134] and chorioamnionitis. 135 Indeed, first trimester placentas from women with obesity show reduced uterine NK cell numbers, which normally comprise ∼70% of the leukocyte population in early human decidua and play a central role in uterine artery remodeling and altered expression of genes in pathways associated with matrix remodeling and growth factor signaling 136 (Fig.…”
Section: Pregravid Obesity and Immune Adaptations In The Placentamentioning
confidence: 99%
“…[128][129][130] For instance, studies have reported decreased IL-35 and IL-9 levels and concurrent drop in CD11c+ myleloid cells and regulatory T cell populations over the course of gestation. 128 Local changes in frequencies, phenotype, and functions of immune cells in the decidua and villi have been attributed in the pathogenesis of several obstetric complications such as preterm labor, 131 PE, [132][133][134] and chorioamnionitis. 135 Indeed, first trimester placentas from women with obesity show reduced uterine NK cell numbers, which normally comprise ∼70% of the leukocyte population in early human decidua and play a central role in uterine artery remodeling and altered expression of genes in pathways associated with matrix remodeling and growth factor signaling 136 (Fig.…”
Section: Pregravid Obesity and Immune Adaptations In The Placentamentioning
confidence: 99%
“…oxidized low-density lipoprotein and hyaluronic acid (Bouças et al, 2017;Yeh et al, 2013). It is assumed that as the result of the presence of bacterial or viral products like Bacterial LPS or viral dsRNA, trophoblast cells through the upregulation of TLRs and subsequent generation of differential chemokine profiles and excessive recruitment of neutrophils, monocytes and NK cells into the maternal-fetal interface trigger abnormal immune responses and further inflammation in PE patients .…”
mentioning
confidence: 99%
“…Growing evidence indicates a role for adaptive immune cell activation in the context of preeclampsia 32 . We therefore assessed circulating components of the adaptive immune system including monocytes, basophils, neutrophils and eosinophils.…”
Section: Resultsmentioning
confidence: 99%